Предмет: Алгебра,
автор: евгения276
решите ,пожалуйста
заранее спасибо
Приложения:
Ответы
Автор ответа:
0
10-x(5-(6+x))= x(x+3) -4x
10- x( 5-6-x)= x^2+3x-4x
10-5x+6x+x^2-x^2-3x+x4x=0
2x+10=0
2x= -10
x= -5
10- x( 5-6-x)= x^2+3x-4x
10-5x+6x+x^2-x^2-3x+x4x=0
2x+10=0
2x= -10
x= -5
Автор ответа:
0
(х+4)²=х(х+3)
х²+8х+16=х²+3х
5х= -16
х= -3,2
10-х(5-(6+х))=х(х+3)-4х
10-х(5-6-х)=х²+3х-4х
10-5х+6х+х²=х²+3х-4х
2х= -10
х= -5
х²+8х+16=х²+3х
5х= -16
х= -3,2
10-х(5-(6+х))=х(х+3)-4х
10-х(5-6-х)=х²+3х-4х
10-5х+6х+х²=х²+3х-4х
2х= -10
х= -5
Похожие вопросы
Предмет: Математика,
автор: sofiasokolova00
Предмет: Математика,
автор: Levi0pravi
Предмет: История,
автор: jannur29
Предмет: География,
автор: dashkevich081
Предмет: Физика,
автор: ananasishe